Menanamkan Nilai-Nilai Moral pada Anak Usia Dini - Pratidarmanastiti, Lusia (Jurnal Orientasi Baru, 2007)
The development of human's life cannot be separated from one's learning experience. Education is a process of learning human values as one experience from the beginning of one's life. A value is uniquely human because it has to do directly with human cognitive ability that enable them to discern and decide priority along with its different qualities of its objects. One of the important values that determines the quality of human dignity is moral value. Therefore, introduction to the moral values needs to be done from the early age. For children, the process of the introduction needs to be adapted to their cognitive development as well as its learning environment and its means. In this way, moral values will be efectively internalized.